Kopu River Rafting Tourism Object Promotion Strategy Based on Tourism Destination Website: Strategi Promosi Objek Wisata Arung Sungai Kopu Berbasis Website Destinasi Wisata - Yuslaini, Nina; Fadhilla, Mutia; Agia, Lintang Nur; Maulidiah, Sri; Wardana, Dema Fito; Maulina, Arifani (Universitas Lancang Kuning, 2024)
This community service activity (PkM) was carried out in Tanjung Village, Koto Kampar Hulu District, Kampar Regency Riau. Tourism Village which is heading towards the concept of Ecotourism. One of the tourist attractions that is in the spotlight and has great potential. This Aung Sungai Kopu tourist attraction provides natural beauty that attracts the attention of tourists. The night of the Anugerah Pesona Indonesia (API) Award for the Kopu River Rafting Tourism Destination which managed to occupy the second position of API Award 202. However, there are many problems such as low visitors and not yet known by the public. To overcome these problems, the PkM team from Riau Islamic University provides solutions with Website-based tourist attraction development strategies. This activity uses the method of socialisation stages, providing assistance, counselling, training and evaluation stages. The results of this activity are that it has a positive impact on Website-based tourism promotion, which is better known to many people, increasing visitors. The community becomes more sophisticated in the use of technology. With so many visitors who can have an impact on socio-economic improvement.